SOSIALISASI PENTINGNYA PLANKTON PADA BUDIDAYA IKAN DI DANAU TOBA - Herna Febrianty Sianipar; Tambos Sianturi; Jhon Sufriadi Purba (Jurnal Abdimas Bina Bangsa, 2022)
This service aims to provide information on the introduction of the importance of the existence of plankton in aquaculture in Lake Toba. This service has been carried out in Parapat, Simalungun Regency with the method of extension and material discussion (exposure and question and answer). The results of this dedication show that many residents and owners of floating fish cages do not understand the role of plankton in fish farming, and not many know the types of plankton. From this dedication, it can be seen that the public interest and owners of floating net cages are very high, and they become more aware of the importance of the existence of plankton in aquaculture in Lake Toba